THE IMPLEMENTATION OF DISCOVERY LEARNING MODEL TO IMPROVE STUDENT ACTIVITIES AND LEARNING ACHIEVEMENT OF PANCASILA AND CIVIC EDUCATION (PPKN) OF 7th GRADE STUDENTS IN SMPN 8 REJANG LEBONG - Parida Ariani; Wachidi Wachidi (UNIB Press, 2018)
The propose of this research is to describe the application of the discovery learning model to improve activeness and learning achievement Pancasila and civic education (PPKn) of 7th Grade Students in SMP 8 Rejang Lebong. This research is classroom action research (PTK) study with mastery of experiments carried out on class students VII as many as 27 students. After observing, it is known that there is an increase in student activity and student learning achievement has increased. The average value of student activity with the increasing category is still quite active and the third cycle is the average value of the activity of students with active categories. while the value of learning achievement Students in the first cycle experienced changes after the pretest and posttest were held. The value of cycle II is also experiencing encouraging development and the value of cycle III is better yet its development reaches a satisfying point. The results thus, the hypothesis reads